2020
DOI: 10.1021/acs.jchemed.0c00855
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating an Online Interactive Video Platform to Optimize Active Learning and Improve Student Accountability through Educational Videos

Abstract: Video learning holds an important place in modern STEM classrooms, but more improvements to the learning experience are needed. In order to introduce active-learning components into assignments, questions are often deployed alongside videos. Unfortunately, many students tend to skip videos entirely and solely answer questions, bypassing valuable assigned content. Edpuzzle is an online video-modifying platform that allows instructors to take videos (both instructor-made as well as pre-existing available videos)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
1
31
0
3
Order By: Relevance
“…Educational videos were designed on the basis of the overall learning outcomes for each lesson. Video scripting and production was done as described in prior studies. In particular, cognitive load theory and the cognitive theory of multimedia learning were used to ensure that cognitive load was effectively managed. Embedded questions were used to enforce problem-solving and immediately provide targeted feedback to students as they progressed through the video activity. These QEVs have been shown to encourage effective learning behaviors and produce greater learning gains than text-based resources or videos without embedded questions. Each video began with a review of general chemistry material (step back) .…”
Section: Program Developmentmentioning
confidence: 99%
“…Educational videos were designed on the basis of the overall learning outcomes for each lesson. Video scripting and production was done as described in prior studies. In particular, cognitive load theory and the cognitive theory of multimedia learning were used to ensure that cognitive load was effectively managed. Embedded questions were used to enforce problem-solving and immediately provide targeted feedback to students as they progressed through the video activity. These QEVs have been shown to encourage effective learning behaviors and produce greater learning gains than text-based resources or videos without embedded questions. Each video began with a review of general chemistry material (step back) .…”
Section: Program Developmentmentioning
confidence: 99%
“…Studies also reported that online learning is able to enhance problem-solving (Yeen-Ju et al, 2015). On the other hand, online learning also promotes accountability (Pulukuri & Abrams, 2020), as well as the decisionmaking ability of learners (Galvis, 2018;Compen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Educational videos were produced on an iPad with Explain Everything, a digital whiteboard app. , Then, the videos were edited in iMovie to improve audio quality and imported into Edpuzzle, , an online platform that was used to insert questions into the videos. The first video (the octet rule, 4 min) had eight embedded questions, the second video (organic Lewis strucures, 7 min) had seven embedded questions, and the third video (bond-line notation, 6 min) had five embedded questions.…”
Section: Methodsmentioning
confidence: 99%